Respiratory syncytial virus epidemiology and clinical severity before and during the COVID-19 pandemic in British Columbia, Canada: a retrospective observational studyResearch in context - Marina Viñeta Paramo; Lilian P.L. Ngo; Bahaa Abu-Raya; Frederic Reicherz; Rui Yang Xu; Jeffrey N. Bone; Jocelyn A. Srigley; Alfonso Solimano; David M. Goldfarb; Danuta M. Skowronski; Pascal M. Lavoie (The Lancet Regional Health. Americas, 2023)
Summary: Background: The COVID-19 pandemic has perturbed the seasonality of respiratory syncytial virus (RSV) infections. However, we lack data on how this impacted the severity of paediatric RSV cases. The objective of this study was to describe the clinical severity of RSV cases before, during and after pandemic measures in British Columbia (BC), Canada. Methods: Retrospective study of RSV cases from September 1st, 2017 to May 15th, 2023, with a review of RSV outcomes in children below 18 years old at BC's paediatric hospital. Temporal changes in RSV cases and hospitalisations were quantified using interrupted time series. Findings: BC experienced only 11 RSV cases (from 95,266 tests) between September 2020 and August 2021. This was followed by a resurgence of 9,529 RSV cases (219,566 tests [4.3% positive tests]) in 2021–22 and 8,215 cases (124,449 tests [6.6% positive tests]) in 2022–23, increased compared to 1,750 cases (48,664 tests [3.6% positive tests]) per corresponding yearly period in 2017–20. From September 2017 to May 2023, the median age of children with RSV at BC Children's Hospital increased from 8.7 [IQR: 2.0–26.0] to 19.6 [3.9–43.7] months per yearly period. More children were hospitalised in 2022–23 (n = 360), compared to 2017–20 (n = 168 per period) and 2021–22 (n = 172). However, we detected no increase in hospitalisations or ICU admissions in children born prematurely or with chronic cardiorespiratory conditions. Interpretation: The increased detection of symptomatic RSV cases in older children in 2021–22 and increased RSV-related hospitalisations in 2022–23 suggest a gradual increase in the pool of immunologically vulnerable children due to a prolonged lack of viral exposure. Funding: Government of Canada via its COVID-19 Immunity Task Force.